Taṣavvuf ke nagẖmāt-i sarmadī : mashhūr Ṣūfī Shuʻarāʻ ke sāz-i ḥayāt aur zaḵẖmah-yi mi̤zrāb ke sāth - Hāshimī, Kāẓim (Shuhūd ʻĀlam Hāshimī : milne ke pate, Kitāb Manzil, 1979)
Short biographies of Urdu Sufi poets; includes an introduction to Sufism in India.